PENERAPAN MODEL PEMBELAJARAN COOPERATIVE TIPE TEAM ACCELERATED INTRUCTION (TAI) UNTUK MENINGKATKAN TANGGUNG JAWAB DAN PRESTASI BELAJAR - Noperiansyah Noperiansyah (UNIB Press, 2022)
This study aims to describe the application of the Cooperative Learning Model Type Team Accelerated Intruction (TAI) learning model and to describe the effectiveness of the Cooperative Learning Model Type Team Accelerated Intruction (TAI) to increase the responsibility and learning achievement of students in class XI SMA Negeri 1 Kikim Timur Lahat. The research method used was Classroom Action Research (PTK) and quasi-experimental. The research subjects were students of class XI IPS 1 semester one academic year 2020/2021 SMA Negeri 1 Kikim Timur Lahat. The quasi-experimental sample is class XI IPS 3 and class XI IPS 2. The number of students for the CAR class is 31 students, for the Experiment class there are 30 students, and for the control class there are 30 students. The data collection method in this study used an observation sheet for the implementation of the Cooperative Learning Model Type Team Accelerated Intruction (TAI), an observation sheet for Increasing Responsibility, and a learning outcome test. The data analysis used tests which consisted of different tests between cycles and different tests of two unrelated samples. The results showed that the application of the Cooperative Learning Model Type Team Accelerated Intruction (Tai) can increase the responsibility and learning achievement of students in class XI SMA Negeri 1 Kikim Timur Lahat and effectively improve student learning outcomes in Economics subjects